2011
DOI: 10.1149/1.3614518
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Temperature Dependence of Trap-Assisted Tunneling in Ge pFET Junctions

Abstract: In this work, the temperature behavior of trap-assisted tunneling (TAT) in Ge pFET junctions selectively grown in STI substrates is evaluated, whereby the impact of the electric field and the threading dislocation density (TDD) is studied for temperatures ranging from 233 to 418 K. The experimental results are compared with the TAT model for Si proposed by [G. A. M. Hurkx, D. B. M. Klaassen, and M. P. G. Knuvers, IEEE Trans. Electron Devices, 39, 331 (1992)], where several parameters (such as the effective mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…In particular it can be responsible of an increase of the leakage current contribute related to the BTB tunneling with the TDD even if the BTB tunneling does not depend explicitly on defect levels [35]. Field-enhanced tunneling mechanisms such as TAT and BTB tunneling have been observed previously in Ge p-i-n photodetectors [36], p + -n Ge junctions for MOSFETs [37], strained SiGe source/drain junctions [38] and Ge pFET junctions [39]. In order to assess the dominant mechanism of transport along TDs in i-Si 0.06 Ge 0.94 /Ge layers, the J-V diode characteristics were measured at temperatures ranging from 210K to 475K.…”
mentioning
confidence: 73%
“…In particular it can be responsible of an increase of the leakage current contribute related to the BTB tunneling with the TDD even if the BTB tunneling does not depend explicitly on defect levels [35]. Field-enhanced tunneling mechanisms such as TAT and BTB tunneling have been observed previously in Ge p-i-n photodetectors [36], p + -n Ge junctions for MOSFETs [37], strained SiGe source/drain junctions [38] and Ge pFET junctions [39]. In order to assess the dominant mechanism of transport along TDs in i-Si 0.06 Ge 0.94 /Ge layers, the J-V diode characteristics were measured at temperatures ranging from 210K to 475K.…”
mentioning
confidence: 73%
“…A further reduction of the depletion width W yields an increase of the maximum electric field at the junction (∼1/W), which promotes field-assisted generation mechanisms like Trap-Assisted Tunneling (TAT) and, finally, Band-To-Band Tunneling (BTBT). [103][104][105] This explains the strong, nearly exponential increase of the leakage current density for doping densities above a few 10 18 cm −3 .…”
Section: Strained Si Layers On a Strain Relaxed Sige Buffer Layer-str...mentioning
confidence: 86%
“…It has been also reported that the BTBT leakage is dominant in a strong electric field of >5 × 10 8 V/m in Ge junctions. 9 Therefore, BTBT leakage current contribution is negligible in this analysis.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…The leakage current has been widely associated with the amount of threading dislocation density (TDD) for Ge photodetectors and for shallow Ge pn junctions. [6][7][8][9][10] Tremendous efforts have been made to decrease dark currents of Ge p-i-n diodes and p + /n junctions by reducing TDDs of Ge layers. The dark current density for Ge p + /n junctions with the TDD of 4.2 × 10 8 cm −2 was reduced by roughly 10× compared to the one with the TDD of 1.6 × 10 10 cm −2 .…”
Section: Introductionmentioning
confidence: 99%